Implementasi project based learning untuk meningkatkan dimensi gotong royong dan kreatif pada mata pelajaran pendidikan pancasila sekolah dasar - Gitaratri Pramudya Widhiasmara; Chumdari Chumdari (Didaktika Dwija Indria, 2025)
This study aims to improve students' collaboration and creativity through the implementation of the Project Based Learning (PjBL) model in Civics Education for fifth-grade students at SD Negeri Danukusuman in the 2024/2025 academic year. The research employed a qualitative approach using Classroom Action Research (CAR), conducted in three cycles and involving 20 students as research subjects. Data were collected through observation, interviews, documentation, and assessment of students’ creative products. The Project Based Learning model was implemented through several stages: determining essential questions, planning the project, creating a schedule, monitoring progress, assessing the outcomes, and evaluating the process. The findings show that the application of this model effectively enhanced students’ collaboration and creativity. The collaboration dimension improved from 66.6% in Cycle I to 80% in Cycle III, while the creativity dimension increased from 66.9% to 78.9%. Project Based Learning, implementation, Civics Education, collaboration, creativity.